Breeding Buckwheat for Increased Levels and Improved Quality of Protein - Luthar, Zlata (Plants (Basel), 2020)
Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) and common buckwheat (Fagopyrum esculentum Moench) are important sources of proteins with balanced amino-acid compositions, and thus of high nutritional value. The polyphenols naturally present in Tartary buckwheat and common buckwheat lower the true digestibility of the proteins. Digestion-resistant peptides are a vehicle for fecal excretion of steroids, and in this way, for bile acid elimination and reduction of cholesterol concentrations in serum. Buckwheat proteins are more effective compared to soy proteins for the prevention of gallstone formation. Tartary and common buckwheat grain that contains appropriate amounts of selenium-containing amino acids can be produced as functional food products. The protein-rich by-products of buckwheat are a good source of bioactive substances that can suppress colon carcinogenesis by reducing cell proliferation. The grain embryo is a rich source of proteins, so breeding buckwheat with larger embryos is a possible strategy to increase protein levels in Tartary and common buckwheat grain. However, chemical analysis of the grain is the most relevant criterion for assessing grain protein levels and quality.